Integration of Synaptic Vesicle Cargo Retrieval with Endocytosis at Central Nerve Terminals - Cousin, Michael A. (Frontiers in Cellular Neuroscience, 2017)
Central nerve terminals contain a limited number of synaptic vesicles (SVs) which mediate the essential process of neurotransmitter release during their activity-dependent fusion. The rapid and accurate formation of new SVs with the appropriate cargo is essential to maintain neurotransmission in mammalian brain. Generating SVs containing the correct SV cargo with the appropriate stoichiometry is a significant challenge, especially when multiple modes of endocytosis exist in central nerve terminals, which occur at different locations within the nerve terminals. These endocytosis modes include ultrafast endocytosis, clathrin-mediated endocytosis (CME) and activity-dependent bulk endocytosis (ADBE) which are triggered by specific patterns of neuronal activity. This review will assess the evidence for the role of classical adaptor protein complexes in SV retrieval, discuss the role of monomeric adaptors and how interactions between specific SV cargoes can facilitate retrieval. In addition it will consider the evidence for preassembled plasma membrane cargo complexes and their role in facilitating these endocytosis modes. Finally it will present a unifying model for cargo retrieval at the presynapse, which integrates endocytosis modes in time and space.